2015
DOI: 10.1074/jbc.m115.645960
|View full text |Cite
|
Sign up to set email alerts
|

IPO3-mediated Nonclassical Nuclear Import of NF-κB Essential Modulator (NEMO) Drives DNA Damage-dependent NF-κB Activation

Abstract: Background: Nuclear import of NEMO is critical for DNA damage-dependent NF-B signaling, but the mechanism remains unknown. Results: IPO3 binds NEMO, promotes its nuclear import, and is critical for DNA damage-dependent NF-B activation. Conclusion: IPO3 is a nonclassical nuclear import receptor for NEMO. Significance: IPO3 is a new player in DNA damage-dependent NF-B signaling with implications in cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…3I and J), which provided further evidence that TRIM37 mediated monoubiqutination of NEMO in the nucleus. Remarkably, the etoposide-induced association of NEMO with Ran, an export receptor and the cargo protein for nuclear export of NEMO (29), was increased in TRIM37-transduced cells but was nearly undetectable in TRIM37 À/À cells, and no interaction of Ran and NEMO/K309A was observed (Fig. 3K).…”
Section: Trim37 Promotes Nuclear Export Of Nemomentioning
confidence: 94%
“…3I and J), which provided further evidence that TRIM37 mediated monoubiqutination of NEMO in the nucleus. Remarkably, the etoposide-induced association of NEMO with Ran, an export receptor and the cargo protein for nuclear export of NEMO (29), was increased in TRIM37-transduced cells but was nearly undetectable in TRIM37 À/À cells, and no interaction of Ran and NEMO/K309A was observed (Fig. 3K).…”
Section: Trim37 Promotes Nuclear Export Of Nemomentioning
confidence: 94%
“…GST-JAK1 NLS fragments were generated by amplifying the fragment spanning nucleotide 982 to 1119 by PCR using either wild type JAK1 or cNLS mutated JAK1 as template, and then subcloning into BamHI and EcoRI restriction sites of pGEX6p-1 vector. Flag-KPNA constructs were previously described (25). HA-KPNAs were generated by amplifying KPNA with PCR (forward primer contains HA tag sequence) and subcloning into BamHI and XhoI restriction sites of pRetroCMV_TO_Hygro vector (eGFP negative).…”
Section: Methodsmentioning
confidence: 99%
“…Classical nuclear import of these large proteins depends on a nuclear localization signal (NLS), generally a short stretch of basic amino acids (either alone or separated by a linker region of 10–12 amino acids), which is directly recognized by one or more of seven importin α subunits (KPNA1-7) (2325). After recognition of its cargos, importin α binds to importin β1 (KPNB1) to form the cargo-importin α –importin β1 complex, which is then transported into the nucleus through the nuclear pore complex.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying this first step of its translocation is not clear, since NEMO lacks a classical nuclear localization signal that would be recognized by importins [32,33]. However, a recent report by Hwang and colleagues demonstrated that NEMO interacts with the importin β family member IPO3 and translocates to the nucleus [34]. At present, we can only speculate but favour a model in which the Ku70/ NEMO interaction modulates NEMO translocation to the nucleus.…”
Section: Discussionmentioning
confidence: 84%